Komunikasi Partisipatif Komunitas Selaras Farm dalam Membangun Kemandirian Ekonomi melalui Program Urban Farming (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the participatory communication strategies implemented by the Selaras Farm Community in building the economic independence of residents through urban farming programs. This study uses a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation. Three key informants were purposively selected: the Chairperson, Coordinator, and Advisor of the Selaras Farm Community. The research data were then analyzed using the Miles and Huberman interactive model (data reduction, data presentation, drawing conclusions), and data validity was tested with triangulation of methods and sources. The results show that the Selaras Farm Community uses five participatory communication strategies: face-to-face and virtual (WhatsApp group) dialogic communication, member training and education, active involvement of residents in program development, transparency in cooperative-based financial management, and building trust through the utilization of local assets. This strategy increases residents' farming skills, reduces household expenditure on food, and provides access to harvests at affordable prices. Participatory communication effectively empowers urban communities to achieve economic independence by optimizing limited land through urban farming. This research contributes to the development of participatory communication theory in the context of urban agriculture and offers a community-based economic empowerment model that can be replicated in other urban residential areas.